(untitled) (Research, Society and Development, 2022)
The aim of the present study was to evaluate the effectiveness of using DAC hydrogel on stable internal fixation materials in surgical procedures. The methodology used to achieve the proposed purpose was a systematic review of the literature currently available and conducted in the MEDLINE databases via PubMed, Scopus, Scielo and Bireme, through controlled and uncontrolled terms, with the use of Boolean operators and Science Descriptors of Health DeCS/MeSH previously chosen. After applying the search strategies and eligibility criteria, 19 articles were included and the characteristics were collected: author, year, type of study, type of sample (human, animals, or laboratory), sample size, antimicrobial used, resorption time of hydrogel, site of hydrogel application, follow-up time, and reported benefits. The interpretation of the evidence obtained in this study allowed us to conclude that the use of DAC hydrogel in surgical procedures with stable internal fixation is effective, safe and should be recommended, and its advantages can be extrapolated to the area of maxillofacial surgery and traumatology. It is evident the need for further studies on the subject, mainly using in vivo samples, in order to establish a standard protocol for care, in addition to establishing reliable long-term results.